On the Effectiveness of Gamified Risk Management Workshops: Evidence from German SMEs - Avo Schönbohm; Alexandra Jülich (Serious Games Society, 2016)
This study analyzes the potential benefits gamification can offer to SMEs in the area of risk management. A structured review of the topic of risk management in SMEs and previous studies of the application of gamification to risk management forms a theoretical framework. A gamified risk management workshop is devised which is used as a treatment for three German SMEs. This article contains a description of the developed workshop, the applied methodology and the respective results. While following a quasi-experimental action research approach, it becomes evident that the gamified workshop has the potential to motivate the participants, increase their knowledge on risk management and foster cognitive and group de-biasing. The findings suggest that gamification can be a valuable tool for SMEs to enhance their risk management process.